Alteraciones emocionales y su influencia en el área conductual de un niño de 9 años de edad con trastorno espectro autista del Centro Integral Infantil Kraaker Babahoyo - Encalada Marin, Gabriela Karina (2022)
Emotional disturbances often occur in childhood, being indicators of the existence of difficulties, they often trigger conditions in several areas of their behavioral, emotional, social and affective development, it is even more complex in children with autism spectrum disorder, Since due to their condition it is difficult for them to assimilate changes, understand situations, process and regulate emotions, becoming frequent the complex interaction of the same in their daily life environment, the present case study has the main function of determining the influence of the alterations emotional in the behavioral area of a 9-year-old boy with autism spectrum disorder, where the aforementioned aspects have become a challenge in his quality of life and that of his parents, causing scenarios in which to aggressive or self-injurious states, conditioning or pigeonholing the child's development in a negative way a.